Perubahan Paradigma Pendidikan Kristen: Analisis Sosiologis terhadap Transformasi Modern - Buka, Pidi (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2023)
This article examines the changing paradigm of Christian education in the context of ongoing modern transformations in society. Through sociological analysis, the article explores the adaptation of Christian education to evolving social, technological and cultural dynamics. Utilising current data and statistics as well as case studies from various sources, the aim of this article is to provide a deeper understanding of the challenges and opportunities faced by Christian educational institutions in the modern era. The findings show that despite significant challenges, Christian education can still transform and maintain its relevance in the changing times. The main purpose of Christian education is to mould the character and morality of individuals through religious teachings. However, with the advancement of technology and globalisation, this paradigm has shifted. Furthermore, shifting social values also contribute to this paradigm shift. Christian education should be able to bridge religious teachings and practical needs in the modern world, so that students are not only academically intelligent, but also have strong characters and who are more effective in implementing relevant and sustainable Christian education in the ever-changing social context.